Classificação do comportamento verbal e aquisição de discriminações condicionais por bebês - Aguiar, Graziele Thomasinho de (2013)
Arbitrary stimuli can be related through conditional discrimination, via procedure Matching-tosample. The procedure can also establish equivalent relations emerge when relations were not directly taught. Such relationships must share three properties: reflexivity, symmetry and transitivity. Authors propose that success in establishing stimulus classes stems from the possibility of appointment by the participant. Among the possibilities to define "name", two stand out in this work: as Tact, towards an object in the environment the person issues an oral word; or as a higher order behavioral relation and bidirectional combining conventional functions of speech and listener. Taking into account the studies presented by both proposals, there appears to be evidence to prove that the appointment is necessary for the establishment of equivalence classes. Therefore, it is important to study participants who have incipient verbal repertoire to test the relationships of verbal behavior in the establishment of conditional discriminations and arbitrary stimulus classes. This study aims to determine the relationship between the verbal repertoire and the acquisition of conditional discriminations in babies up to 30 months old. This was done / assessments will be carried language development of participants through the Denver II and Operational Portage Inventory. Five teaching conditional discrimination procedures and tests of naming and equivalence were conducted with thirteen participants from 13 to 28 months. The verbal repertoire of these participants were classified according to the Skinner s taxonomy, and were also recorded behaviors listener and follow rules during teaching sessions and moments of free play. As a result, it was observed that all babies emitted echoic, tact and mands during session, eight participants learned the conditional discrimination proposals, all they learned discrimination vocalized the names of the experimental stimuli at some point, five participants underwent tests of symmetry and transitivity with familiar stimuli, two participants tested, none passed tests of equivalence. This indicates that the conditional discrimination learning depends on methodological aspects employees; verbal behavior, including the appointment of the names used in teaching auditoryvisual discrimination, can facilitate this learning. However, there is still no conclusive data on the need of the ability of appointment to the establishment of equivalence classes of stimuli.